'We should have been told what would happen': Children's and parents' procedural knowledge levels and information-seeking behaviours when coming to hospital for a planned procedure. (March 2022) - Bray, Lucy; Appleton, Victoria; Sharpe, Ashley
Children continue to be poorly prepared and informed about clinical procedures, despite increased evidence of the worth of preparation and the availability of information resources. This study used a concurrent mixed-methods approach to explore the information accessed by children and their parents before attending hospital for a procedure. Information was collected separately from 40 children (aged between 8 and 12 years) and their parents using a paper booklet to examine self-reported perceived procedural knowledge and information-seeking behaviours. Data were analysed using descriptive statistics and content analysis techniques. The findings indicate that many children (70%, n = 28) and their parents (65%, n = 26) have low procedural knowledge levels. The majority of children (85%, n = 36) reported not receiving or seeking information about their procedure, despite identifying a desire and preference for more information. This study shows a mismatch between the current provision of procedural information and children and parents' expectations that information will be provided directly to them by health professionals. In order for this 'information hole' to be filled, there needs to be a concerted effort to develop and systematically use meaningful information materials and for children and their parents to have the opportunity to discuss their procedural knowledge with health professionals.